WATERSCAPES IN WALLMAPU: LESSONS FROM MAPUCHE PERSPECTIVES. - Aigo, Juana del Carmen; Skewes, Juan Carlos; Bañales-Seguel, Camila; Riquelme Maulén, Wladimir; Molares, Soledad; Morales, Daniela; Ibarra, Maria Ignacia; Guerra, Debbie (Geographical Review)
This article reflects on the multiple worlds generated around waterscapes in the diverse Mapuche territory, Wallmapu. We contrast the responses of three Mapuche communities to external interventions and water availability in the Chimehuin and Lepá rivers in Argentina, and the Huenehue River in Chile. The comparison reveals the nature of Mapuche waterscapes, the tensions provoked by the global economy, and its impacts on water management. Mapuche communities establish an intersubjective relationship with water, securing and protecting their water supply. Waterscapes are constituted as living entities where human and nonhuman stories converge and on which biocultural memory is periodically enriched in its response to a changing environment. We conclude that coexistence between Mapuche and non-Mapuche worlds, however diverse the communities might be, is sustained through equivocal relations and partial connections. Established views of water management in Wallmapu could be greatly enriched by the Mapuche's views and practices.